Ikaros family members from the agnathan Myxine glutinosa and the urochordate Oikopleura dioica: Emergence of an essential transcription factor for adaptive immunity - Cupit, P.; Hansen, J.; McCarty, A.; White, Greg; Chioda, M.; Spada, F.; Smale, S.; Cunningham, C. (American Association of Immunologists, 2003)
The Ikaros multigene family encodes a number of zinc finger transcription factors that play key roles in vertebrate hemopoietic stem cell differentiation and the generation of B, T, and NK cell lineages. In this study, we describe the identification and characterization of an Ikaros family-like (IFL) protein from the agnathan hagfish Myxine glutinosa and the marine urochordate Oikopleura dioica, both of which lie on the evolutionary boundary between the vertebrates and invertebrates. The IFL molecules identified in these animals displayed high conservation in the zinc finger motifs critical for DNA binding and dimerization in comparison with those of jawed vertebrates. Expression of the IFL gene in hagfish was strongest in blood, intestine, and gills. In O. dioica, transcription from the IFL gene was initiated at or around the time of hatching and maintained throughout the life span of the animal. In situ hybridization localized O. dioica IFL expression to the Fol cells, which are responsible for generating the food filter of the house. Biochemical analysis of the DNA binding and dimerization domains from M. glutinosa and O. dioici IFLs showed that M. glutinosa behaves as a true Ikaros family member. Taken together, these results indicate that the properties associated with the Ikaros family preceded the emergence of the jawed vertebrates and thus adaptive immunity.